Role of alvarado score in diagnosis of acute appendicitis - Md Fardhus, -; Sharfuzzaman, AMSM; Dewan, Md Nayeem; Rab, Joy Zakharia (Journal of Surgical Sciences, 2020)
Background: Appendicitis may be associated with morbidity and occasionally mortality. If failed to diagnose early, the situation may become more complicated. Objective: To validate the role of Alvarado score in diagnosis of acute appendicitis. Methods: A total of 282 patients with clinically diagnosed acute appendicitis were included in this study. Patients were examined thoroughly, investigated and managed accordingly. The relevant data collected and analyzed. Results: Out of 282 patients, surgical procedures were performed in 59.57% of the patients. The overall negative Appendectomy rate was 9.52%, and the percentage of Positive Predictive Value (PPV) for Alvarado score was 92.26%. Conclusion: Our study validates the Alvarado score as fast, simple and reliable diagnostic tool for acute appendicitis. Journal of Surgical Sciences (2017) Vol. 21 (2): 94-98